Inovasi Pelaksanaan Pembelajaran Guru PAI di Madrasah Tsanawiyah - Syarbaini Syarbaini; Nurmawati Nurmawati; Salminawati Salminawati (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This article aims to find out how to innovate lesson plans, implement learning, inhibiting and supporting factors for implementing learning as well as innovative use of media in implementing Islamic education teacher learning at MTs Nurul Khairiyah Deli Serdang. This type of research is qualitative, with descriptive analysis. The samples in this study were class VIII students of MTs Nurul Khairiyah Deli Serdang. Data collection tools using interviews, observation, and documentation. Analyzing the researcher uses two stages, namely data processing and data analysis. In terms of analyzing data, researchers also use two methods, namely pre-field analysis and field analysis. From the two methods, conclusions will be drawn from the results of the research conducted. The results showed that the learning method using a combination of several learning methods for one material in one meeting was seen as more effective and efficient in conveying the material. Choosing appropriate learning media and utilizing existing learning resources in Madrasahs and developing selected teaching materials can attract student learning interest. Existing media is accompanied by methods, and strategies that can help the selected media.